Konsep Diri dengan Komunikasi Interpersonal - Suak, Azalia Vania Velma; Anderson, Elisa; Manoppo, Arlien (Universitas Malahayati, 2023)
ABSTRACT In nursing activities, communication is the most fundamental, as it is the main work tool for every nurse in providing nursing care. Self-concept is a very determining factor in interpersonal communication because everyone behaves according to their own self-concept.This study aims to determine the relationship between self-concept and interpersonal communication among the Faculty of Nursing students at Klabat University.The method used in this research is cross-sectional, involving 229 respondents through consecutive sampling technique with the Spearman's rank statistical test. The results of the univariate analysis showed that the description of self-concept was in the moderate category, and the description of interpersonal communication was in the moderate category. The results of the bivariate analysis found that there was a value of p = 0,000 (<0,05) and a correlation coefficient of r = 0,568. There was a significant relationship between self-concept and interpersonal communication among the Faculty of Nursing students at Klabat University. that the relationship is in the moderate category and has a positive direction, where the higher the self-concept, the higher the interpersonal communication. It is hoped that the results of this study can provide information for students so they can develop their self-concept and interpersonal communication in a positive direction. And it is expected for future researchers to conduct research on other factors, such as family support and knowledge about interpersonal communication, that can influence interpersonal communication. Keywords: Self-Concept, Interpersonal Communication ABSTRAK Di dalam aktivitas keperawatan komunikasi adalah hal yang paling mendasar, yaitu sebagai alat kerja utama bagi setiap perawat dalam pemberian asuhan keperawatan. Konsep diri merupakan faktor yang sangat menentukan dalam komunikasi interpersonal, karena setiap orang bertingkah laku sesuai dengan konsep dirinya. Penelitian ini bertujuan untuk mengetahui hubungan antara konsep diri dengan komunikasi interpersonal mahasiswa Fakultas Keperawatan di Universitas Klabat. Metode yang digunakan dalam penelitian ini adalah cross-sectional yang melibatkan 229 responden melalui teknik consecutive sampling dengan uji statistik spearman’s rank. Hasil analisis univariat menunjukkan bahwa gambaran konsep diri termasuk dalam kategori sedang dan gambaran komunikasi interpersonal termasuk dalam kategori sedang. Hasil analisis bivariat didapati nilai p = 0,000 (<0,05) serta nilai koefisien korelasi r = 0,568. Terdapat hubungan yang signifikan antara konsep diri dan komunikasi interpersonal pada mahasiswa Fakultas Keperawatan di Universitas Klabat. Keeratan hubungan adalah sedang dan bersifat positif, dimana semakin tinggi konsep diri maka semakin tinggi pula komunikasi interpersonal. Diharapkan hasil penelitian ini dapat menjadi informasi bagi para mahasiswa agar dapat mengembangkan konsep diri dan komunikasi interpersonal ke arah yang baik. Dan diharapkan untuk peneliti selanjutnya untuk melakukan penelitian mengenai faktor-faktor lain yang dapat mempengaruhi konsep diri maupun komunikasi interpersonal. Kata Kunci: Konsep Diri, Komunikasi Interpersonal